Sol-Gel Erbium-Doped Silica-Hafnia Planar and Channel Waveguides - Gonçalves, Rogéria R.; Carturan, Giovanni; Zampedri, Luca; Ferrari, Maurizio; Armellini, Cristina; Chiasera, Alessandro; Mattarelli, M.; Moser, Enrico; Montagna, Maurizio; Righini, Giancarlo C.; Pelli, Stefano; Nunzi Conti, Gualtiero; et al. (SPIE, the international society for optics and photonics, 2003)
Erbium activated SiO2 -HfO2 planar waveguides, doped with Er3+ concentrations ranging from 0.01 to 4 mol%, were prepared by sol-gel method. The films were deposited on v-SiO2 and silica-on-silicon substrates using dip-coating technique. The waveguides show high densification degree, effective intermingling of the two film components, and uniform surface morphology. The waveguide deposited on silica-on-silicon substrates shows one single propagation mode at 1.5μm, with a confinement coefficient of 0.81 and an attenuation coefficient of 0.8 dB/cm at 632.8nm. Emission in the C-telecommunication band was observed at room temperature for all the samples upon continuouswave excitation at 980 nm or 514.5 nm. The shape of the emission band corresponding to the 4I13/2 → 4I15/2 transition is found to be almost independent both on erbium content and excitation wavelength, with a FWHM between 44 and 48 nm. The 4I13/2 level decay curves presented a single-exponential profile, with a lifetime ranging between 1.1 - 6.6 ms, depending on the erbium concentration. Infrared to visible upconversion luminescence upon continuous-wave excitation at 980 nm was observed for all the samples. Channel waveguide in rib configuration was obtained by etching the active film in order to have a well confined mode at 1.5 μm.
Keywords: Channel waveguides; Erbium; Luminescence; Silica-hafnia; Sol-gel planar waveguides; Deposition; Etching; Morphology; Semiconductor doping; Silicon wafers; Sol-gels; Substrates; Wavelength division multiplexing; Planar waveguides; Optical waveguides